STUDYING THE INHIBITORY EFFECTS OF ACETAMINOPHEN (PARACETAMOL), AND SALICYLATE DRUG (ASPEGIC) ON THE ACTIVITY OF CREATINE KINASE - Ali, Perry H; Husain, Jinan; Husain, Jinan; Hashim, Iman (Al-Nahrain Journal of Science, 2010)
We have studied for the first time in Iraq, the effect of aspegic and paracetamol on the activityof creatine kinase in the sera of 25 premenopausal health women our results revealed that inthe presences of increasing concentrations of aspegic and paracetamol the activity of creatinekinase is inhibited and the inhibition is concentration dependant and independent respectively.The kinetic parameter of creatine kinase was measured (Vmax= 133.3.00 IU/L,Km=(2.13 } 0.2 mM).Aspegic act as reversible competitive inhibitor for CK(150 } 3.3 IU/L ,Km= 2.4 } 0.4mM) and paracetamol act as reversible uncompetitive inhibitor for creatine kinase(87.72 } 2.1 IU/L, Km=2.02 } 0.33 Mm).